Effects of test anxiety on mathematics achievement scores of second year Nakorn Phanom Comprehensive School students in Thailand - Kulasing, Siriporn (1977)
The main purpose of the study was to find out the relation between mathematics achievement scores and test anxiety. It also sought to find the difference in mathematics achievement test scores of students with different levels of anxiety. A questionnaire and a mathematics test were used as the instruments for gathering data. The Pearson product-formula was used to find the relation between test anxiety and achievement score for mathematics. The analysis of variance was used to determine whether the mean scores of the groups differed. The results showed that there is a positive relation between mathematics achievement scores and test anxiety.